The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.6001/zemesukiomokslai.v20i3.2742
|View full text |Cite
|
Sign up to set email alerts
|

Returns to scale in the Lithuanian family farms: A quantitative approach

Abstract: The paper analysed the returns to scale and scale elasticity prevailing in the Lithuanian family farms. The analysis was based on the farm-level data. Specifically, the three farming types were considered, viz. crop, livestock, and mixed farming. The non-parametric method, data envelopment analysis, was employed to define the production frontier and compute the estimates of the scale elasticity. The inefficient observations were projected on the production frontier and analysed both in input and output orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…In the third group are regions with mixed production (M). A similar principle for dividing agricultural holdings or FADN regions has been used in other research reports, including (Baležentis and Valkauskas, 2013;Smędzik, 2010;Špička, 2014). A different way of dividing the studied objects, depending on the value of the technological efficiency index, was used by (Błażejczyk-Majka et al, 2011).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the third group are regions with mixed production (M). A similar principle for dividing agricultural holdings or FADN regions has been used in other research reports, including (Baležentis and Valkauskas, 2013;Smędzik, 2010;Špička, 2014). A different way of dividing the studied objects, depending on the value of the technological efficiency index, was used by (Błażejczyk-Majka et al, 2011).…”
Section: Methodsmentioning
confidence: 97%
“…Other examples include (Burja, 2011), a study focusing on Romanian agriculture; (Zimmermann and Heckelei, 2012), a report on European dairy farms; (Akande, 2012), an analysis of FADN regions; and (Atici, 2012), an article on Turkish agriculture. Moreover, (Baležentis and Valkauskas, 2013) examines the efficiency of selected farms in Lithuania; (Brummer and Thiele, 1999) looks at ways of studying aggregated efficiency on the basis of data on German farms; (Buckley and Carney, 2013) focuses on the analysis of efficiency in Irish agriculture; (Błażejczyk-Majka et al, 2011Špička, 2014) look at FADN regions; and (Smędzik, 2010) focuses on Polish farms. In addition to nonparametric methods, parametric methods are also used in research reports such as (Caldas and Rebelo, 2003) on Portugal's Douro region; (Kaditi and Nitsi, 2009) on Greek agriculture; (Barnes et al, 2010) on British agriculture; and (Marzec and Pisulewski, 2013) on dairy farms in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Taigi buvo sudaryta dalimis tiesinė empirinė gamybos funkcija. Detalesnis tyrimo metodikos aprašymas pateikiamas atitinkamuose moksliniuose darbuose (Banker, Thrall, 1992;Färe et al, 1983;Førsund, Hjalmarsson, 2004;Førsund et al, 2007;Zschille, 2012;Baležentis et al, 2013;Baležentis, Valkauskas, 2013). Siekiant įvertinti Lietuvos žemės ūkio transformacijas po įstojimo į Europos Sąjungą, buvo nagrinėtas 2004-2009 m. laikotarpis.…”
Section: Pav Gamybinė Funkcija Produktyvumo Matai Ir Optimalus Veikunclassified
“…According to a survey of the economic activity of the respondent farms, in 2009 the most technically efficient farms are large farms with more than 100 ha (Vinciūnienė et al, 2009). When looking at farm size modelling using the return of scale analysis method, LAEI researchers (Baležentis et al, 2013) also state that "the optimal farm size for crop production is around 280 ha, for mixed farming -200 ha and for livestock production -125 ha". In 2001, an analysis of the land holdings of 224 farms larger than 40 ha, carried out at the Lithuanian University of Agriculture, showed that the land holdings of large farms (with an average of 94 ha of agricultural land) are not compact: it was found that some of the farms' land parcels are not located in a single massive and that the average distance to the fields of the farmer's own land is 3.2 km, and the distance to the fields of the entire land area of the farms is 4.38 km (Aleknavičius et al, 2002).…”
Section: Introductionmentioning
confidence: 99%